Gaming to Safety: Exploring Feedback Gamification for Mitigating Driver Distraction. (September 2016) - Xie, Jeanne Y.; Chen, Huei-Yen Winnie; Donmez, Birsen
The risk of crash or near-crash significantly increases when drivers make long off-road glances to engage in distracting tasks. Providing drivers with feedback that integrates elements of game design could increase driver motivation for adopting safer behaviors. In an ongoing between-subjects simulator study with young drivers ( n =29 reported in this paper), we compare four conditions for off-road glance behaviors: no feedback, real-time feedback system, post-drive feedback system (real-time feedback + post-drive feedback), and gamification feedback system (real-time feedback + post-drive feedback + game design elements). Shorter average glance duration and less frequent risky (≥2 s) glances to an in-vehicle display were observed for the post-drive system, compared to no feedback and real-time feedback, and for the gamification system, compared to no feedback. Although no added benefit of gamification over the post-drive feedback system was observed for these eye glance metrics, longer-term exposure and assessment could show improvements to be more stable with the inclusion of game design elements.